Mixed-methods research of motivational processes in workers' adoption of healthy behavior - Kayoko Ishii; Hiroko Sumita; Hitomi Nagamine; Kumiko Morita (BMC, 2024)
Abstract Background In occupational health, the maintenance and promotion of workers' health, especially lifestyle motivation-based interventions, have gained considerable attention and are actively implemented. Motivational theories include self-determination theory, and some studies focus on healthy lifestyles. However, the effectiveness of health promotion interventions varies depending on the health awareness and motivation of the participants. Therefore, this study aimed to clarify the processes by which workers are motivated to improve their health and to identify the need for and type of support according to their motivation. Methods Using a mixed-research design, an initial questionnaire survey of 94 employees (mean age = 40.97 ± 9.65) at a multicenter company in Japan, followed by semi-structured interviews with 16 employees (mean age = 40.13 ± 9.45) from the high- and low-motivation groups, were conducted. Multiple regression analysis followed by modified grounded theory-based analysis of the results of the first stage was used and the quantitative and qualitative results were integrated. Results In the first stage, autonomous motivation scores were predicted by the behavioral change stage and relatedness satisfaction/frustration. The second stage revealed that "the process of reflecting and managing one's own health while receiving support and feedback for maintaining and improving health" was the motivational process of workers. Result integration revealed that motivation increased through repeatedly escaping and adjusting to real problems and situational coping until the behavioral change. Despite interruptions during behavioral change, receiving feedback from others could increase motivation and continued behavioral change. Conclusion Regardless of their level of motivation for health behaviors, workers indicated that support from others was essential. The nature of this support was found to range from providing information to offering feedback. Interventions individualized by the identified process could enable customized motivation-driven health guidance.